2016
DOI: 10.1111/anae.13544
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anti-emetic doses of dexamethasone on postoperative blood glucose levels in non-diabetic and diabetic patients: a prospective randomised controlled study

Abstract: SummaryThere are few data regarding postoperative hyperglycaemia in non-diabetic compared with diabetic patients following postoperative nausea and vomiting prophylaxis with dexamethasone. Eighty-five non-diabetic patients and patients with type-2 diabetes were randomly allocated to receive intravenous dexamethasone (8 mg) or ondansetron (4 mg). Blood glucose levels were measured at baseline and then 2, 4 and 24 h following induction of anaesthesia. In nondiabetic patients, the mean (SD) maximum blood glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
85
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 24 publications
2
85
1
2
Order By: Relevance
“…We thank Tien et al for their prospective randomised study on dexamethasone and blood glucose levels in diabetic and non-diabetic patients [1]. We would like to invite the authors to address several questions that we have.…”
Section: Magnanmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Tien et al for their prospective randomised study on dexamethasone and blood glucose levels in diabetic and non-diabetic patients [1]. We would like to invite the authors to address several questions that we have.…”
Section: Magnanmentioning
confidence: 99%
“…) for patients administered low-flow anaesthesia using the formula: (inspired O 2 fractionÀend-tidal O 2 fraction) 9 minute ventilation [1], but we suggest that the alveolar minute ventilation, not the total minute ventilation, should be used for this calculation. Total minute ventilation includes dead-space ventilation, which does not take part in gas exchange.…”
mentioning
confidence: 99%
“…Patel and Fregene for their interest in our study [1]. While some studies have reported an increase in blood glucose following the use of hetastarch [2], others did not show a difference in glucose concentrations between those who received hetastarch compared with lactated Ringers's [3] or with gelatin solutions [4].…”
mentioning
confidence: 92%
“…Tien et al reported an increase in postoperative blood sugar levels after anti-emetic doses of dexamethasone were used in diabetic and non-diabetic patients [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation